A multi-scale study on the movement ecology of Afrotropical waterbirds - Henry, Dominic A W (Percy FitzPatrick Institute of African Ornithology, 2016)
Understanding the processes and mechanisms governing animal movement is a fundamental goal in ecology. Processes driving movement can occur across multiple spatiotemporal scales and have important consequences for the structure and dynamics of populations, communities and ecosystems. The study of movement provides insights into the ecological resources and habitats necessary for persistence of species and communities. It also provides a theoretical and applied basis from which to formulate informed conservation plans. Waterbirds in semiarid southern Africa are an ideal study group for understanding interactions between movement and environmental factors because they exhibit a wide range of movement strategies and are located within a landscape in which resources are characterised by high levels of spatiotemporal variability. Emphasis has been placed on understanding movement phenomena from individually-tracked animals, but cases which consider this approach in conjunction with traditional community ecology perspectives are rare. In this thesis I explored questions of movement in both individuals and communities, and argue that an integrated multi-scale approach is necessary to advance our broader understanding of movement in waterbirds. In the first part of the study I addressed an individual-level movement perspective. I used fine-scale telemetry data from 35 individually tracked Egyptian Geese Alopochenaegyptiaca and Red-billed Teal Anas erythrorhyncha with novel analytical techniques to explore questions of trade-offs in habitat selection, functional responses and whether movement responses to landscape resources are reactive or prescient. My findings suggested that, at the home-range scale, both forage optimisation and predation risk were limiting factors of movement and habitat selection of Egyptian Geese. I also showed for the first time that waterbirds exhibit functional responses in relation to changes in the availability of habitat types. I subsequently showed that the proximate drivers of waterfowl movement are the dynamics of rainfall and primary productivity. Egyptian Geese and Red-billed Teal were able to perceive and respond to temporal shifts in resource conditions prior to habitat patch occupation. This in turn suggested that their movements in semi-arid landscapes are underpinned by an intimate knowledge of the local environment and that waterfowl exhibit a complex behavioural movement strategy. In the second part of the study I used waterbird count data collected from wetlands in KwaZulu-Natal, South Africa, to address the community-level movement perspective.